Integral formed inductor and its manufacturing method
Patent Information
- Application Number
- TW114104918
- Authority / Receiving Office
- TW · TW
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-02-10
- Publication Date
- 2026-08-16
- Estimated Expiration
- 2045-02-09
AI Technical Summary
High-current circuit inductors made of alloy composite materials face issues such as deformation of copper wire due to excessive pressure, leading to increased resistance and high residual losses, along with a risk of short circuits, which affect power supply efficiency.
A molded inductor composed of a core column with a specific iron-based alloy composition, a wound coil, a magnetic sheet, and a residual magnet, coated with an insulating and rust-proof layer, to reduce eddy currents and maintain high permeability, using materials like phenyl oxy resin and silicon micro powder.
The solution reduces eddy current loss and increases permeability, allowing for lower resistance copper wire usage, thereby improving inductor efficiency and reducing power loss.
Smart Images

Figure TWG2TA001072190_001 
Figure TWG2TA001072190_002 
Figure TWG2TA001072190_003
Abstract
Description
Technical Field
[0001] This invention relates to the field of electronic equipment technology, specifically to a wire-wound type integrally molded inductor. Prior Technology
[0002] Against the backdrop of increasingly stringent energy conservation and environmental protection requirements across the entire electronics industry, improving power supply efficiency is a key development direction. High-efficiency power supplies reduce energy loss, lower equipment operating costs, and help reduce heat generation. One of the biggest sources of loss in power supplies is inductance. Currently, the mainstream high-current circuit inductors are integrally molded inductors made of alloy composite materials. However, because their coils need to be pressed together with the magnet, excessive pressure cannot be used, leading to deformation of the copper wire, increasing its resistance. Simultaneously, the presence of significant stress results in high residual losses and a risk of short circuits.
[0003] Therefore, the composition, process design, and structural design of integrally molded inductor alloy powder are essential for improving the material's performance by maintaining low loss at high frequencies and low loss at high power. Thus, it is necessary to develop new high-frequency, high-current, low-loss composite materials and their integrally molded inductor technology. Summary of the Invention
[0004] The present invention solves the above problems by controlling the material composition and structure.
[0005] The technical means adopted in this invention is to provide a molded inductor, which includes: The core column is a composite material made of iron-based alloys, with a composition of 92.1–96.43 wt% iron (Fe), 3.5–7.5 wt% silicon (Si), 0.01–0.1 wt% boron (B), 0.01–0.1 wt% aluminum (Al), and 0.05–0.2 wt% chromium (Cr). A coil, wound around the core post; A magnetic sheet, made of a composite material composed of an iron-based alloy, has the same material composition as the core column. The magnetic sheet is disposed at the bottom of the core column, and the coil is bent and fastened to the bottom of the magnetic sheet to form a bottom electrode. A residual magnet, which covers the core and the coil and exposes the bottom electrode, is composed of a mixed powder of iron-based alloy, iron-based amorphous nanocrystals, and carbonyl iron powder; An insulating and rust-proof layer is applied to the surface of the remaining magnet. The insulating and rust-proof layer is a composite coating composed of phenyl oxy resin, phenolic epoxy resin, and silicon micro powder.
[0006] Furthermore, the present invention also provides a method for manufacturing the aforementioned inductor, comprising the following steps: providing the core post; winding the coil around the core post; placing the magnetic sheet at the bottom of the core post, and forming the bottom electrode by bending and fastening the coil to the bottom of the magnetic sheet, wherein the core post, the coil, and the bottom electrode constitute a winding; covering the remaining magnet with the winding; and disposing the insulating and rust-proof layer on the remaining magnet.
[0007] The advantages of this invention are that the Si in the core material forms an insulating layer inside the metal crystal to reduce internal eddy currents. At the same time, the insulating layer enriched with Al and Cr on the surface of the material particles formed at high temperature further reduces eddy currents. Meanwhile, the high Fe content allows the material to maintain high permeability. In addition to obtaining a material with low eddy current loss, the permeability of the core 1 is increased, so copper wire with lower resistance can be used to achieve the same inductance value, thereby reducing inductor loss. At the same time, the residual magnet 3 further reduces eddy current loss at high frequencies through the combination of nanocrystals and ultrafine alloys, thereby reducing inductor loss and improving the conversion efficiency of power circuits using the inductor of this invention. Simple Explanation of the Diagram
[0008] Figure 1 is a perspective view of the inductor of the present invention; Figure 2 is a perspective view of some components of the inductor of the present invention; Figure 3 is a perspective view of some components of the inductor of the present invention from another angle; Figure 4 is a cross-sectional view of the inductor of the present invention; Figure 5 is a flowchart of the manufacturing method of the inductor of the present invention. Implementation
[0009] The following, in conjunction with the accompanying drawings and embodiments of the present invention, further illustrates the technical means employed by the present invention to achieve its intended purpose. The drawings have been simplified for illustrative purposes only, and the structure or method of the present invention is explained by describing the relationship between the elements and components of the present invention. Therefore, the elements shown in the drawings are not presented in actual quantity, actual shape, actual size, or actual proportion. The size or size proportion has been enlarged or simplified to provide a better illustration. The actual quantity, actual shape, or actual size proportion has been selectively designed and configured, and the detailed element layout may be more complex.
[0010] Please refer to Figures 1 to 5. The method for preparing the integrally molded inductor of the present invention includes the following steps: providing a core post 1 (S10); winding a coil 2 around the core post 1 (S20); placing a magnetic sheet 5 at the bottom of the core post 1, and forming a bottom electrode 4 by bending and fastening the coil 2 to the bottom of the magnetic sheet 5 (S30), wherein the core post 1, the coil 2, and the bottom electrode 4 constitute a winding; covering the winding with a residual magnet 3, and exposing the bottom electrode 4 (S40); and providing an insulating and rust-proof layer 6 on the residual magnet 3 (S50). The core post 1 occupies 20 vol% to 50 vol% of the volume of the residual magnet 3. The materials of the core post 1 and the magnetic sheet 5 of the inductor are composite materials composed of iron (Fe)-based alloys. Its material composition is 92.1~96.43wt% Fe, 3.5~7.5wt% silicon (Si), 0.01~0.1wt% boron (B), 0.01~0.1wt% aluminum (Al), and 0.05~0.2wt% chromium (Cr). The particle size of the constituent material is 5~53um, and the particle surface has a composite oxide layer of silicon oxide, iron oxide, and chromium oxide of 10~100nm. The height of the core column 1 is 60%~90% of the inductor height. The residual magnet 3 of the inductor is composed of a mixture of iron-based alloy, iron-based amorphous nanocrystals, and carbonyl iron powder. The composition can be a mixture of a main material of 89.7~94.97wt% Fe, 3.0~5.5wt% Si, 2.0~4.5wt% B, 0.01~0.1wt% phosphorus (P), 0.01~0.1wt% copper (Cu), and 0.01~0.1wt% nickel (Ni) with a 3um~5um iron-based alloy. The iron-based alloy consists of 92.1~96.43wt% Fe, 3.5~7.5wt% Si, 0.01~0.1wt% B, and 0.01~0.1wt% P. The nanocrystal material accounts for 60wt%~80wt% of the powder weight, and the iron-based alloy accounts for 20wt%~40wt% of the powder weight. The nanocrystals have two coating layers on their surface. The first layer is a mixed layer of oxides such as alumina and silicon oxide, with a thickness of 8-15 nm. The second layer is composed of organic resin, specifically a mixed coating layer of epoxy resin and silicone resin. The epoxy resin has a softening temperature of less than 100℃, while the silicone resin has a thermal decomposition temperature of greater than 300℃. The coating layer thickness is 100-200 nm, and the mass ratio of epoxy resin to silicone resin is 1:1 to 3:1. The iron-based alloy surface has a single coating layer with a thickness of 50-150 nm. This coating layer is a mixture of phenolic resin and silicone resin, with the phenolic resin having a softening temperature of less than 100℃ and the silicone resin having a thermal decomposition temperature of greater than 300℃. The mass ratio of phenolic resin to silicone resin is 1:1 to 3:1.An insulating and anti-rust layer 6 is attached to the surface of the inductor. This insulating and anti-rust layer 6 is a composite coating composed of phenyloxy resin, phenolic epoxy resin, and silicon micropowder. The coating thickness is 10-30 μm. Phenoxy resin accounts for 50-80 wt% of the insulating layer material, and its molecular weight is greater than 8000. Phenolic epoxy resin accounts for 10-30 wt% of the insulating layer material, and its glass transition temperature is greater than 150℃. Silicon micropowder accounts for 10-20 wt% of the insulating layer material, and its particle size is 8-20 nm.
[0011] The technical solutions in the embodiments of the present invention will be clearly and completely described below. The described embodiments are only some embodiments of the present invention, and not all embodiments.
[0012] [Example] [1] [:]
[0013] The integrally molded inductor of the present invention comprises a core post 1, a coil 2, a residual magnet 3, and a magnetic sheet 5. The coil 2 is wound around the core post 1 of the magnetic core and is bent and fastened to the bottom of the magnetic sheet 5 to form a bottom electrode 4. The core post 1 occupies 50 vol% of the volume of the residual magnet 3. The core post 1 and the magnetic sheet 5 of the inductor are made of a composite material composed of an iron-based alloy. The material composition is 92.1 wt% Fe, 7.5 wt% Si, 0.1 wt% B, 0.1 wt% Al, and 0.2 wt% Cr. The particle size of the constituent material is 5~53 μm, and the surface of the particles has a 10 nm composite oxide layer of silicon oxide, iron oxide, and chromium oxide. The height of the core post 1 is 90% of the height of the inductor. The residual magnet 3 of the inductor is made of a main material consisting of 94.97 wt% Fe, 3.0 wt% Si, 2.0 wt% B, 0.01 wt% P, 0.01 wt% Cu, and 0.01 wt% Ni, mixed with a 5 μm iron-based alloy. The iron-based alloy consists of 96.43 wt% Fe, 3.5 wt% Si, 0.01 wt% B, and 0.01 wt% P. The nanocrystalline material accounts for 60 wt% of the powder weight, and the iron-based alloy accounts for 40 wt% of the powder weight. The nanocrystal surface has two coating layers. The first layer is a mixed layer of alumina and silicon oxide, 15 nm thick. The second layer is composed of an organic resin, specifically a mixed coating layer of epoxy resin and silicone resin. The epoxy resin has a softening temperature of 70°C, and the silicone resin has a thermal decomposition temperature of 330°C. The coating layer is 100 nm thick, and the mass ratio of epoxy resin to silicone resin is 1:1. The iron-based alloy surface has a single coating layer, 50 nm thick, composed of a mixture of phenolic resin and silicone resin. The phenolic resin has a softening temperature of 80°C, and the silicone resin has a thermal decomposition temperature of 330°C. The mass ratio of phenolic resin to silicone resin is also 1:1. An insulating and anti-rust layer 6 is attached to the surface of the inductor. The insulating and anti-rust layer 6 is a composite coating composed of phenyloxy resin, phenolic epoxy resin and silicon micro powder. The coating thickness is 30 μm. Phenoxy resin accounts for 50 wt% of the insulating layer material and has a molecular weight of 8700. Phenoxy epoxy resin accounts for 30 wt% of the insulating layer material and has a glass transition temperature of 160℃. Silicon micro powder accounts for 20 wt% of the insulating layer material and has a particle size of 20 nm.
[0014] [Example] [2] [:]
[0015] The integrally molded inductor of the present invention comprises a core post 1, a coil 2, a residual magnet 3, and a magnetic sheet 5. The coil 2 is wound around the core post 1 of the magnetic core and is bent and fastened to the bottom of the magnetic sheet 5 to form a bottom electrode 4. The core post 1 occupies 20 vol% of the volume of the residual magnet 3. The core post 1 and the magnetic sheet 5 of the inductor are made of a composite material composed of an iron-based alloy. The material composition is 96.43 wt% Fe, 3.5 wt% Si, 0.01 wt% B, 0.01 wt% Al, and 0.05 wt% Cr. The particle size of the constituent material is 5~53 μm, and the surface of the particles has a 100 nm composite oxide layer of silicon oxide, iron oxide, and chromium oxide. The height of the core post 1 is 60% of the height of the inductor. The residual magnet 3 of the inductor is composed of a main material consisting of 89.7 wt% Fe, 5.5 wt% Si, 4.5 wt% B, 0.1 wt% P, 0.1 wt% Cu, and 0.1 wt% Ni, mixed with a 3 μm iron-based alloy. The iron-based alloy consists of 92.1 wt% Fe, 7.5 wt% Si, 0.1 wt% B, and 0.1 wt% P. The nanocrystalline material accounts for 80 wt% of the powder weight, and the iron-based alloy accounts for 20 wt% of the powder weight. The nanocrystalline surface has two coating layers: the first layer is a mixed layer of oxides such as alumina and chromium oxide, with a thickness of 8 nm; the second layer is composed of organic resin, specifically a mixed coating layer of epoxy resin and silicone resin. The epoxy resin has a softening temperature of 60℃, and the silicone resin has a thermal decomposition temperature of 360℃. The coating layer thickness is 200 nm, and the mass ratio of epoxy resin to silicone resin is 3:1. The iron-based alloy surface has a coating layer with a thickness of 150 nm. This coating layer is a mixture of phenolic resin and silicone resin. The phenolic resin has a softening temperature of less than 65℃, while the silicone resin has a thermal decomposition temperature of 360℃. The mass ratio of phenolic resin to silicone resin is 3:1. An insulating and anti-rust layer 6 is attached to the inductor surface. This insulating and anti-rust layer 6 is a composite coating composed of phenyloxy resin, phenolic epoxy resin, and silicone micropowder. The coating thickness is ~30 μm. Phenoxy resin accounts for 80 wt% of the insulating layer material, with a molecular weight of 9000. Phenoxy epoxy resin accounts for 10 wt% of the insulating layer material, with a glass transition temperature of 170℃. Silicon micropowder accounts for 10 wt% of the insulating layer material, with a particle size of 8 nm.
[0016] [Example] [3] [:]
[0017] The integrally molded inductor of the present invention comprises a core post 1, a coil 2, a residual magnet 3, and a magnetic sheet 5. The coil 2 is wound around the core post 1 of the magnetic core and is bent and fastened to the bottom of the magnetic sheet 5 to form a bottom electrode 4. The core post 1 occupies 20 vol% to 50 vol% of the volume of the residual magnet 3. The core post 1 and the magnetic sheet 5 of the inductor are made of a composite material composed of an iron-based alloy. The material composition is 94.35 wt% Fe, 5.5 wt% Si, 0.05 wt% B, 0.05 wt% Al, and 0.15 wt% Cr. The particle size of the constituent material is 5-53 μm, and the surface of the particles has a 50 nm composite oxide layer of silicon oxide, iron oxide, and chromium oxide. The height of the core post 1 is 75% of the height of the inductor. The residual magnet 3 of the inductor is made of a main material consisting of 91.75 wt% Fe, 4.7 wt% Si, 3.4 wt% B, 0.05 wt% P, 0.05 wt% Cu, and 0.05 wt% Ni, mixed with a 4 μm iron-based alloy. The iron-based alloy consists of 93.8 wt% Fe, 6.1 wt% Si, 0.05 wt% B, and 0.05 wt% P. The nanocrystalline material accounts for 70 wt% of the powder weight, and the iron-based alloy accounts for 30 wt% of the powder weight. The nanocrystals have two coating layers on their surface. The first layer is a mixed layer of oxides such as alumina and silicon oxide, with a thickness of 12 nm. The second layer is composed of organic resin, specifically a mixed coating layer of epoxy resin and silicone resin. The epoxy resin has a softening temperature of 80℃, and the silicone resin has a thermal decomposition temperature of 370℃. The coating layer is 150 nm thick, and the mass ratio of epoxy resin to silicone resin is 2:1. The iron-based alloy surface has a single coating layer with a thickness of 90 nm. This coating layer is a mixture of phenolic resin and silicone resin, with the phenolic resin having a softening temperature of 80℃ and the silicone resin having a thermal decomposition temperature of 370℃. The mass ratio of phenolic resin to silicone resin is also 2:1. An insulating and anti-rust layer 6 is attached to the surface of the inductor. The insulating and anti-rust layer 6 is a composite coating composed of phenyloxy resin, phenolic epoxy resin and silicon micro powder. The coating thickness is 20 μm. Phenoxy resin accounts for 70 wt% of the insulating layer material and has a molecular weight of 9000. Phenoxy epoxy resin accounts for 15 wt% of the insulating layer material and has a glass transition temperature of 170℃. Silicon micro powder accounts for 15 wt% of the insulating layer material and has a particle size of 12 nm.
[0018] [Comparative Example] [1] [:]
[0019] The fabrication method of the integrally molded inductor of Comparative Example 1 includes the following steps: The inductor is composed of an inductor core 1, a coil 2, a residual magnet 3, and a magnetic sheet 5. The coil 2 is wound around the core 1 of the magnetic core and is bent and fastened to the bottom of the magnetic sheet 5 to form a bottom electrode 4. The core 1 accounts for 50 vol% of the volume of the residual magnet 3. The materials of the inductor core 1, the magnetic sheet 5, and the residual magnet 3 are composed of a main material with a composition of 94.97 wt% Fe, 3.0 wt% Si, 2.0 wt% B, 0.01 wt% P, 0.01 wt% Cu, and 0.01 wt% Ni, mixed with a 5 μm iron-based alloy. The iron-based alloy consists of 96.43 wt% Fe, 3.5 wt% Si, 0.01 wt% B, and 0.01 wt% P. The nanocrystalline material accounts for 60 wt% of the powder weight, and the iron-based alloy accounts for 40 wt% of the powder weight. The nanocrystal surface has two coating layers. The first layer is a mixed layer of alumina and silicon oxide, 15 nm thick. The second layer is composed of an organic resin, specifically a mixed coating layer of epoxy resin and silicone resin. The epoxy resin has a softening temperature of 70°C, and the silicone resin has a thermal decomposition temperature of 330°C. The coating layer is 100 nm thick, and the mass ratio of epoxy resin to silicone resin is 1:1. The iron-based alloy surface has a single coating layer, 50 nm thick, composed of a mixture of phenolic resin and silicone resin. The phenolic resin has a softening temperature of 80°C, and the silicone resin has a thermal decomposition temperature of 330°C. The mass ratio of phenolic resin to silicone resin is also 1:1. An insulating and anti-rust layer 6 is attached to the surface of the inductor. The insulating and anti-rust layer 6 is a composite coating composed of phenyloxy resin, phenolic epoxy resin and silicon micro powder. The coating thickness is 30 μm. Phenoxy resin accounts for 50 wt% of the insulating layer material and has a molecular weight of 8700. Phenoxy epoxy resin accounts for 30 wt% of the insulating layer material and has a glass transition temperature of 160℃. Silicon micro powder accounts for 20 wt% of the insulating layer material and has a particle size of 20 nm.
[0020] The product's performance was evaluated. The product dimensions were 6.0 mm (length) x 6.0 mm (width) x 1.8 mm (height). The inductance of the magnetic ring sample (1V / 1MHz) and the inductance at 100A current were measured using a 3260B LCR meter and a thermistor. The product loss (1MHz / 1A) was measured using a SY8218. Table 1. Performance Comparison of Examples and Comparative Examples (0420 Inductor) Test Project Parameter Units Example 1 Example 2 Example 3 Comparative Example 1 L μH 2.21 2.18 2.2 1.76 L1 (current = 5A) μH 1.83 1.87 1.85 1.31 Pc (loss) mW twenty three 25 19 39
[0021] The 0618 inductors prepared in the comparative examples and the comparative examples, with the same inductance value, exhibit superior losses compared to the comparative examples. Therefore, they offer a lower power consumption advantage in practical applications, thereby improving the conversion efficiency of the product's application circuits. This demonstrates that component control and structural design are crucial for low-loss inductors.
[0022] The above description is merely an embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above by way of embodiment, it is not intended to limit the present invention. Anyone skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.
[0023] 1: Core 2: Coil 3: Residual magnets 4: Bottom electrode 5: Magnetic disc 6: Insulating and rust-proof layer
Claims
1. A molded inductor comprising: a core made of a composite material composed of an iron-based alloy, the material composition being 92.1~96.43wt% iron (Fe), 3.5~7.5wt% silicon (Si), 0.01~0.1wt% boron (B), 0.01~0.1wt% aluminum (Al), and 0.05~0.2wt% chromium (Cr); a coil wound around the core; a magnetic sheet made of a composite material composed of an iron-based alloy, the material composition being the same as that of the core, the magnetic sheet being disposed at the bottom of the core, and the coil being bent and fastened to the bottom of the magnetic sheet to form a bottom electrode; and a residual magnet covering the core and the coil, exposing the bottom electrode, the residual magnet being composed of a mixed powder of an iron-based alloy, iron-based amorphous nanocrystals, and carbonyl iron powder; An insulating and rust-proof layer is applied to the surface of the remaining magnet. The insulating and rust-proof layer is a composite coating composed of phenyl oxy resin, phenolic epoxy resin, and silicon micro powder.
2. The integrally molded inductor as described in claim 1, wherein the core column occupies 20 vol% to 50 vol% of the volume of the remaining magnet.
3. The integrally molded inductor as claimed in claim 1, wherein the particle size of the constituent materials of the core and the magnetic sheet is 5~53um, wherein the particle surface has a composite oxide layer of silicon oxide, iron oxide and chromium oxide of 10~100nm, and wherein the height of the core is 60%~90% of the height of the inductor.
4. The integrally molded inductor as claimed in claim 1, wherein the residual magnet is made of a material composed of a main material having a composition of 89.7-94.97 wt% Fe, 3.0-5.5 wt% Si, 2.0-4.5 wt% B, 0.01-0.1 wt% phosphorus (P), 0.01-0.1 wt% copper (Cu), and 0.01-0.1 wt% nickel (Ni) mixed with a 3-5 μm iron-based alloy, wherein the iron-based alloy has a composition of 92.1-96.43 wt% Fe, 3.5-7.5 wt% Si, 0.01-0.1 wt% B, and 0.01-0.1 wt% P, wherein the nanocrystalline material accounts for 60-80 wt% of the powder weight, and the iron-based alloy accounts for 20-40 wt% of the powder weight. The nanocrystals have two coating layers on their surface. The first layer is a mixed layer of oxides such as alumina and silicon oxide, with a thickness of 8-15 nm. The second layer is composed of organic resin, which is a mixed coating layer of epoxy resin and silicone resin. The epoxy resin has a softening temperature of less than 100℃, and the silicone resin has a thermal decomposition temperature of greater than 300℃. The coating layer thickness is 100-200 nm, and the mass ratio of epoxy resin to silicone resin is 1:1-3:
1. The iron-based alloy surface has a coating layer with a thickness of 50-150 nm. This coating layer is a mixture of phenolic resin and silicone resin, where the phenolic resin has a softening temperature of less than 100℃, and the silicone resin has a thermal decomposition temperature of greater than 300℃. The mass ratio of phenolic resin to silicone resin is 1:1-3:
1.
5. The integrally molded inductor as described in claim 1, wherein the thickness of the insulating and anti-rust layer is 10~30µm, wherein phenoxy resin accounts for 50wt%~80wt% of the insulating layer material and the molecular weight of the phenoxy resin is greater than 8000, wherein phenolic epoxy resin accounts for 10wt%~30wt% of the insulating layer material and the glass transition temperature of the phenolic epoxy resin is greater than 150℃, wherein silicon micropowder accounts for 10wt%~20wt% of the insulating layer material and the particle size of the silicon micropowder is 8~20nm.
6. A method for manufacturing an integrally molded inductor as described in any one of claims 1 to 5, comprising the following steps: Provide the core post; wind the coil around the core post; place the magnetic sheet at the bottom of the core post, and form the bottom electrode by bending and fastening the coil to the bottom of the magnetic sheet, wherein the core post, the coil, and the bottom electrode constitute a winding; cover the remaining magnet with the winding; and provide the insulating and rust-proof layer on the remaining magnet.